AGILITY ORGANISASI DAN PRAKTIK HUMAN RESOURCES MANAGEMENT TERHADAP DAMPAK DISRUPTION SEMASA COVID 19 - Harimurti Wulandjani; Harlis Setiyowati (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2021)
Human capital or human resources (HR) as the most effective driver for developing agile consequences and HRM (Human Resources Management) practices. Furthermore, as the key to improving company performance. The author has tried to recount and combine the various viewpoints and ideologies of many researchers. The purpose of this research is to study employee involvement, organizational performance through HRM practices during the Covid 19 disruption. creating new markets. Fourth, products / services are more accessible or accessible to users. Fifth, everything has become smarter, more time-saving and more accurate.